Tragičnost položaja in delovanja pomožnega škofa dr. Vekoslava Grmiča - Peršak, Tone (Časopis za zgodovino in narodopisje, 2023)
The article aims to interpret the efforts of Dr. Vekoslav Grmič, the Auxiliary Bishop of Maribor, in promoting dialogue between the Roman Catholic Church and the authorities in Slovenia from 1968 to 1980. Despite being a leading figure in these efforts, Dr. Grmič was later marginalized and socially isolated, both by his own will and by the will of Pope John Paul II. However, he was still able to speak in public. Given the deafness of the environment in which he was active, the ecclesiastical authorities’ opposition, and the political authorities’ ignorance, his fate was tragic. He was a tragic hero, something which he also realized.
Keywords: Cerkev; Grmič, Vekoslav; politika; poslanstvo; socialni čut; tragični junak; tragičnost; vera; Zveza komunistov